Randomized study comparing vitamin D3 and 1α‐Hydroxyvitamin D3 in combination with pegylated interferon/ribavirin therapy for chronic hepatitis C. Issue 9 (September 2015) - Omori‐Mizuno, Yoshie; Nakayama, Nobuaki; Inao, Mie; Funyu, Junji; Asabe, Shinichi; Tomita, Kengo; Nishikawa, Kou; Hosoda, Yasuo; Tanaka, Masahiko; Hashimoto, Yoshiaki; Yakabi, Koji; Koshima, Yohei; et al.
Abstract Background and Aim An intention‐to‐treat prospective randomized study was carried out to compare the potentiation of antiviral efficacies between cholecalciferol, non‐activated vitamin D3 supplement, and alfacalcidol, activated 1α‐Hydroxyvitamin D3 [1α (OH)‐vitamin D3]. Methods Chronic hepatitis patients with genotype 1b hepatitis C virus (HCV) infection showing serum HCV‐RNA levels greater than 5 Log IU/mL received oral administration of cholecalciferol (2000 IU/day) or alfacalcidol (0.5 μg/day) for 4 weeks, and then they were given pegylated interferon (Peg‐IFN)‐α2a plus ribavirin therapy in combination with either vitamin D3 for 48 or 72 weeks according to the response‐guided manner. Results A total of 36 patients were evaluated. Serum 25‐hydroxyvitamin D3 [25(OH)‐D3] levels were increased only in patients in the cholecalciferol group during the lead‐in vitamin D administration, and the levels at 4 weeks were higher in these patients than in those in the alfacalcidol group (P < 0.001), while serum 1α, 25‐dihydroxyvitamin D3 [1α, 25(OH)2‐D3] levels were not different between both groups. Rapid virological response was obtained in six (33%) patients in the cholecalciferol group; the ratio was higher than that in the alfacalcidol group (one patient; 6%, P < 0.05). Serum HCV‐RNA level decline at 4 weeks of combined Peg‐IFN‐α2a plus ribavirin therapy compared with the baseline levels were greater in the cholecalciferol group (4.6 Log IU/mL) than in the alfacalcidol group (3.5 Log IU/mL) (P < 0.05), when four patients showing null response to the therapy was excluded. However, both complete early virological response and sustained viral response rates were not different between both groups. Conclusion Cholecalciferol produced superior potentiation of the antiviral activity than alfacalcidol only during the initial periods of combined Peg‐IFN‐α2a plus ribavirin therapy through upregulation of serum 25(OH)‐D3 levels.